Language As Key Factor Of Long-Term Value Creation In Mergers And Acquisitions In The Telecommunications Sector - J Navio-Marco; M Solorzano-Garcia; A. Urue\~na (International Telecommunications Society (ITS), 2015)
This article analyzes long-term value creation or destruction in mergers and acquisitions in the telecommunications sector. After characterizing the market targeted by the analysis (telecommunications) and discussing and selecting the most suitable long-term methodology, we will make an econometric analysis of telecommunications M&A in the period from 1995 to 2010. The research will focus on telephone companies or operators as leading players in the sector. Based on this econometric analysis, we clearly found evidence of value destruction (2000-2010) using different methodologies, and value creation in the M&A using same language in the involved companies. According with the type of operations, some political recommendations can be established. This is the first econometric study devoted to long-term value creation in telecommunications after the liberalization of the telecom market.
Keywords: 330; mergers and acquisitions; long-term; value creation; telecommunications; abnormal returns; language